Influência do ruído de tráfego em edifícios e proposta de solução desenvolvida com auxílio de modelos numéricos - GUIMARAES, Erick Van Casseb (Universidade Federal do Pará, 2014)
In Brazil, the number of houses and apartments that suffer the influence of noise pollution is quite large. Currently, this question gained important local attention when Belém-PA was elected the “National Capital of Noise” for several years in a row, according to data obtained by the IBGE. Among the most common types of noise pollution, the biggest complaint of society is regarding traffic noise, which is inherent to the daily life of any great city. While the traffic noise concerns increase, so does the preoccupation with a degree of discomfort from the population, justifying the development of means to quantify and reduce such discomfort beyond the means of regulations for this situation by Brazilian standards. Therefore, the condition of traffic noise, while a principal agent of annoyance for the population in which it refers to the noise pollution, it comes to justify the necessity to realize a study that aims at the development of elements of construction by means of new geometrics and composition of existing materials that minimize the penetration of traffic noise to the internal environments of these constructions. So, this work presents the results of studies of the acoustic behavior in situated constructions next to roads of great flow of vehicles which suffer interferences caused by the generation of traffic noise. So far, there were measures carried out in the field of a 25 story building in advanced stages of construction and was chosen as the subject for this study, which represents a numerical modeling of this building with the help of the software ODEON.